C3 plant carbon isotope discrimination does not respond to CO2 concentration on decadal to centennial timescales. Issue 5 (22nd November 2020) - Stein, Rebekah A.; Sheldon, Nathan D.; Smith, Selena Y.
Summary: Plant carbon isotope discrimination is complex, and could be driven by climate, evolution and/or edaphic factors. We tested the climate drivers of carbon isotope discrimination in modern and historical plant chemistry, and focus in particular on the relationship between rising [CO2 ] over Industrialization and carbon isotope discrimination. We generated temporal records of plant carbon isotopes from museum specimens collected over a climo‐sequence to test plant responses to climate and atmospheric change over the past 200 yr (including Pinus strobus, Platycladus orientalis, Populus tremuloides, Thuja koraiensis, Thuja occidentalis, Thuja plicata, Thuja standishii and Thuja sutchuenensis ). We aggregated our results with a meta‐analysis of a wide range of C3 plants to make a comprehensive study of the distribution of carbon isotope discrimination and values among different plant types. We show that climate variables (e.g. mean annual precipitation, temperature and, key to this study, CO2 in the atmosphere) do not drive carbon isotope discrimination. Plant isotope discrimination is intrinsic to each taxon, and could link phylogenetic relationships and adaptation to climate quantitatively and over ecological to geological time scales.